Comprehending Meningioma Signaling Cascades Using Multipronged Proteomics Approaches & Targeted Validation of Potential Markers - Mukherjee, Shuvolina; Biswas, Deeptarup; Gadre, Rucha; Jain, Pooja; Syed, Nelofer; Stylianou, Julianna; Zeng, Qingyu; Mahadevan, Anita; Epari, Sridhar; Shetty, Prakash; Moiyadi, Aliasgar; Roy Ball, Graham; et al. (Frontiers in Oncology, 2020)
Meningiomas are one of the most prevalent primary brain tumors. Our study aims to obtain mechanistic insights of meningioma pathobiology using mass spectrometry-based label-free quantitative proteome analysis to identifying druggable targets & perturbed pathways for therapeutic intervention. Label-free based proteomics study was done from tissue samples of 21 patients & 8 non-tumor controls, which were followed up with Phosphoproteomics to identify the kinases and phosphorylated components of the perturbed pathways. In silico approaches revealed perturbations in extracellular matrix remodeling & associated cascades. To assess the extent of influence of Integrin & PI3K-Akt pathways, we used an ILK inhibitor on patient-derived meningioma cell line and performed a transcriptomic analysis of the components. Furthermore, we designed targeted proteomics assays, which to the best of our knowledge for very first-time enabled identification of peptides from 54 meningioma patients via SRM assay to validate the key proteins emerging from our study. This resulted in the identification of peptides from CLIC1, ES8L2, AHNK many of which are receptors & kinases and are difficult to be characterized using conventional approaches. Furthermore, we were also able to validate proteins like NEK9 and CKAP4, which have been reported to be associated with meningioma pathobiology. This work not only offers an extensive overview of meningioma landscape, it also cross-validates several novel candidate markers that are associated with meningioma pathobiology. Further, it lays the foundation to design peptide-based validation assays, which will pave way for further integration of proteomics data in existing modalities of patient management.